Perilunate Dislocations: Current Treatment Options. Issue 9 (12th September 2022) - Fisher, Nina D.; Bi, Andrew S.; De Tolla, Jadie E.
Abstract : ➢ Approximately 25% of all patients who sustain perilunate dislocations present in a delayed fashion. ➢ While management of acute injuries is relatively well-described, treatment of chronic injuries can be complex and there is a paucity of scientific evidence to guide management. ➢ Treatment options include open reduction internal fixation, proximal row carpectomy, scaphoid or lunate excision with or without arthrodesis, and total wrist arthrodesis, although indications vary based on chronicity of injury and patient factors. ➢ The purpose of this article was to determine the quality of evidence supporting surgical options for the treatment of these injuries.